Personality traits and career strategies as determinants of career satisfaction - Tan, Fee Yean; Khulida Kirana Yahya, (Penerbit Universiti Kebangsaan Malaysia, 2011)
This study examined individual's personality traits and career strategies that influence career satisfaction. Based on social cognitive career theory and an integrated model of proactive behaviours, the study proposed that career strategies would mediate the relationship between individual's personality traits and career satisfaction. Data were gathered through questionnaire survey of insurance agents (n = 531) located in the Northern States of Peninsular Malaysia. Regression results revealed that individual's personality traits and career strategies were correlated with career satisfaction. Results also provided partial support for the mediating role of career strategies (interpersonal attraction, seeking social support and self-nomination) on the relationship between individual's personality traits (extraversion) and career satisfaction. The findings were discussed and implications were also put forward.